2010
DOI: 10.1371/journal.pone.0011132
|View full text |Cite
|
Sign up to set email alerts
|

Defective Lamin A-Rb Signaling in Hutchinson-Gilford Progeria Syndrome and Reversal by Farnesyltransferase Inhibition

Abstract: Hutchinson-Gilford Progeria Syndrome (HGPS) is a rare premature aging disorder caused by a de novo heterozygous point mutation G608G (GGC>GGT) within exon 11 of LMNA gene encoding A-type nuclear lamins. This mutation elicits an internal deletion of 50 amino acids in the carboxyl-terminus of prelamin A. The truncated protein, progerin, retains a farnesylated cysteine at its carboxyl terminus, a modification involved in HGPS pathogenesis. Inhibition of protein farnesylation has been shown to improve abnormal nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 42 publications
4
55
0
Order By: Relevance
“…4F–J). Previous literatures reported that releasing progerin from the nuclear membrane by farnesyltransferase inhibitor treatment partially rescued the gene expression and morphological defects in HGPS cells (Capell et al ., 2005, 2008; Capell & Collins, 2006; Gelb et al ., 2006; Cao et al ., 2007; Wang et al ., 2007; Marji et al ., 2010). Indeed, we find that not only the nuclear morphology but also the chromatin organization and gene expression are improved in the MB‐treated HGPS nucleus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4F–J). Previous literatures reported that releasing progerin from the nuclear membrane by farnesyltransferase inhibitor treatment partially rescued the gene expression and morphological defects in HGPS cells (Capell et al ., 2005, 2008; Capell & Collins, 2006; Gelb et al ., 2006; Cao et al ., 2007; Wang et al ., 2007; Marji et al ., 2010). Indeed, we find that not only the nuclear morphology but also the chromatin organization and gene expression are improved in the MB‐treated HGPS nucleus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LMNA binds directly to hypophosphorylated RB1 during the G 1 phase of the cell cycle and protects RB1 from proteasomal degradation (36). Gene expression profiling of HGPS fibroblasts also demonstrated that Rb1 mRNA levels are low in HGPS cells and that RB1 is the only known LMNA-interacting protein whose expression is abnormal compared with that of control cells (37). Results of additional studies using a farnesyltransferase inhibitor are consistent with the hypothesis that loss of RB1 is the primary direct effect of the LMNA mutation studied.…”
Section: Figurementioning
confidence: 98%
“…Nuclear morphology is altered in laminopathies and is linked to lamin A and B defects (11)(12)(13)(14)(15). Lamins localize at the NE and maintain the nuclear shape; they also form dynamic invaginations that connect the NE with the cytoplasm and chromatin and regulate DNA events (2)(3)(4)(5)(6)(7)(8)41).…”
Section: Pi3k␤ Expression Is Necessary For Ne Integritymentioning
confidence: 99%
“…Nuclear lamina proteins interact with chromatin and with other proteins to regulate NE integrity as well as cell responses, such as cell cycle progression and gene expression. Lamin B1 associates with PCNA (proliferating cell nuclear antigen) to control DNA replication (41) and binds Nup to control NPC incorporation in the NE (21); lamin A/C associates with and stabilizes Rb (retinoblastoma protein) and restrains the G 1 /S transition (15,43) (Fig. 3A).…”
Section: Pi3k␤ Expression Is Necessary For Ne Integritymentioning
confidence: 99%